The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jonm.12695
|View full text |Cite
|
Sign up to set email alerts
|

Nurse managers’ perceptions of care environment supporting older people’s ability to function in nursing homes

Abstract: The results provide a framework for nurse managers for analysing and developing the care environment supporting residents' ability to function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…Effective management of changed life circumstances can be a source of hopefulness to older people living in nursing homes. Suhonen et al ( 2019 ) noted that practices that increase connections and interaction among people are needed for better resident outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Effective management of changed life circumstances can be a source of hopefulness to older people living in nursing homes. Suhonen et al ( 2019 ) noted that practices that increase connections and interaction among people are needed for better resident outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is important as in demonstrating the importance and interconnectedness of person‐centredness and perceptions of individuality, it suggests that an improvement of the PCC climate may help in the provision of individualised nursing care. In turn, this would enable older people's further independence and self‐management (Nordin et al, 2017; Suhonen et al, 2018). Additionally, the association makes it possible to use the climate of person‐centredness a contributor for perceptions of individuality in the care and that person‐centredness can potentiate such perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Providing residents with private bedrooms with private bathrooms was fundamental to a good quality of life [22]. Homelike environments could also be created when residents were allowed to decorate private bedrooms with their favourite personal belongings and materials, such as photographs [14,21,26]. RNs also reported that residents would feel more at home when a right to privacy was granted and respected [17].…”
Section: Indoor Spacesmentioning
confidence: 99%